Total signal intensity of ultrasound laboratory vertical artifacts: a semi-quantitative tool - Leote, Joao (2024)
Quantitative approaches to improve lung ultrasound (LUS) vertical artifacts (VA) interpretation using total signal intensity (ITOT) are not widely available for clinical practice. In this study, we aimed to i) develop a mathematical algorithm to extract ITOT as a post-hoc LUS analysis and ii) confirm ITOT utility by conducting laboratory VA research using an in vitro model with different acoustic channels. The ITOT was extracted from static and conventional LUS imaging recorded from in vitro models after varying the amount of water content or the pores size of the phantom, compared to a control condition. The defined algorithm was able to calculate the ITOT from all phantoms. Mean ITOT showed statistically significantly different values across phantom categories. We demonstrate that ITOT may be able to differentiate the in vitro acoustic channels formed by increased water content from those with small size pores. However, the utility of this semi-quantitative tool in clinical practice or other LUS imaging data sets remains unclear.